THE EFFECT OF QUALITY OF WORK LIFE ON ORGANIZATIONAL COMMITMENT (Case Study at PT. Bank BRI Branch Manado) - Wongkar, Valenia F.; Saerang, David P. E.; Pandowo, Merinda . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Quality of Work Life are the important thing when employee achieve the main goals, with support by good human resource management employees reach the purpose of the organization to create a great commitment. Therefore, good quality of work life create a high organizational commitment. This research aimed to analyze simultaneously and partially effect of quality of work life (fair and adequate payment, safe and healthy workplace, growth and security, development of human capabilities, social integration) on organizational commitment at PT. Bank BRI Branch Manado. Multiple regression analysis and quantitative method are used to this research. Respondent consists of 50 employees of PT. Bank BRI Branch Manado through questionnaire. The result data processed using SPSS 20 and result showed that quality of work life (fair and adequate payment, safe and healthy workplace, growth and security, development of human capabilities, social integration) has a significant influence to organizational commitment simultaneously. Partially growth and security, development of human capabilities are significant influence organizational commitment. PT. Bank BRI Branch must maintain the strategic programs to improve the quality of human resources working life in organizations.Â Keywords : quality of work life, organizational commitmentÂ